Emotions of The Main Character in The Film Sang Martir by Helfi Kardit: Literary Psychological Analysis - Siallagan, Reynaldo (L'Geneus : The Journal Language Generations of Intellectual Society, 2020)
The emergence of literature is motivated by the existence of a basic human urge to express his existence through the literary works he creates. Therefore, not a few people are competing to carve their existence by producing various types of literary works. The large number of literary works that were born from the hands of modern and classical writers cannot be separated from the analysis and study of linguists and literary experts. The study of literary works can be viewed from various points of view, one of which is from the character's point of view. The purpose of writing this thesis is to show and obtain a picture of the main character's emotions in the form of joy, anger, fear and sadness as well as the causes of the emotions of the main character in the film Sang Mortar by Helfi Kardit. Research on the film Sang Mortar by Helfi Kardit uses literary psychology theory with the psychoanalysis of Sigmund Freud with qualitative research methods. Data collection techniques in this study used library study techniques and descriptive analysis techniques as data analysis techniques. The results of this study can be concluded that, Rangga's character's emotions are evidenced by Rangga's attitudes, reactions, words and treatment of the situation or problem at hand. The causes of emotion in the character Rangga in the film Sang Mortar by Helfi Kardit, among others, are the causes of emotional joy, namely communicating partners, unexpected things and problem solving. The cause of angry emotions, namely unacceptability and feeling controlled. The cause of the emotion of fear, namely feeling that safety is threatened. Cause the emotion of sadness.